Español Correspondence in the process of identifying the photographs of León Martínez-Fortún Erlés in the photographic collection of the Martínez-Fortún Fonds of the Municipal Archive of Valladolid - Martínez-Fortún Medrano, Eduardo (Revista General de Información y Documentación, 2025)
In 2019, the Martínez-Fortún family donated his family archives to the Valladolid Municipal Archives, with documentation ranging from the fifteenth to the twentieth century. One of its most remarkable pieces is a collection of photographs from the nineteenth and twentieth centuries of a considerable historical value for the information it provides about its members, the activities they developed and their participation in the Spanish and Cuban society, economy and politics of the time. As we carry out the task of describing the photographs, it becomes necessary to identify, above all, the people who appear in the snapshots. The fact that the collection is part of the Martínez-Fortún archives has facilitated this task of identification, since among the letters that make up the series Correspondence we find some that can be related to photographs in the collection. The relationship between photographic and textual documents, something natural in the organic set of documents that constitutes an archive, gives us the possibility of providing the images with an archival and historical context. In this way, in addition to recognising the people photographed, they can be placed in the coordinates of time and space. The present article studies the relationship between the letters in the family collection and the photographs of León Martínez-Fortún Erlés, one of the first members of the family for whom we have images in the collection, in order to contextualize them temporally and spatially.
Keywords: Valladolid Municipal Archives; Martínez-Fortún Fonds; correspondence; photographic collection; identification